Strength parameters in judo athletes: An aprroach using hand dominance and weight categories - Detanico, D.; Budal Arins, F.; Dal Pupo, J.; dos Santos, S. G. (Human Movement, 2012)
This study aimed to relate strength parameters of the judogi pull test and countermovement jump (CMJ), and body fat with body mass and to compare strength parameters in the judogi pull test between the dominant and non-dominant hands. Methods. Eighteen male judokas took part in this study. The following parameters were analysed: maximal force (Fmax), time to maximal force (TFmax), rate of force development (RFD) and rate of peak force decrement (RPFD) of the dominant and nondominant hands during the pull test. Jump height (Hmax), power, Fmax, peak velocity (PV) and RFD in the CMJ were also measured. A t-test and Pearson`s correlation were used. Results. Fmax (absolute and relative) and RFD were greater for the dominant hand, whereas RFPD was greater for the non-dominant hand during the pull test. There was a significant correlation only between absolute Fmax and body mass (r = 0.51) in the pull test. For the CMJ, relative power (r = -0.57), Hmax (r = -0.49) and PV (r = -0.53) were negatively correlated with body mass, while absolute Fmax (r = 0.84) and power (r = 0.69) were positively correlated with body mass. A significant correlation between body mass and body fat (r = 0.88) was found. Conclusions. There are differences in maximal and explosive force and the rate of peak force decrement between the dominant and non-dominant hand. Absolute values of power and maximal force increased according to body mass (and, therefore, a higher weight category); however jump performance decreased with an increase in body mass (weight category).